2014
DOI: 10.1109/tdei.2014.004120
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the discharge activity across GFRP material due to salt deposit under transient voltages by adopting OES and LIBS technique

Abstract: In the present study, breakdown characteristics of a glass fiber reinforced plastic (GFRP) with different salt deposit densities (SDD) under standard lightning impulse (LI)/ switching impulse (SI) voltages are studied. Optical emission during discharge process and the discharge current are measured simultaneously. It is observed that flashover voltage (FOV) reduces with increase in salt deposit density on GFRP material under LI/SI (irrespective of the polarity of applied voltage) voltages. It is also observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Kumar 12 found that flashover voltage reduced with the increasing of salt deposit density on GFRP material, and the flashover voltage under negative switching impulse is less compared with positive switching impulse.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar 12 found that flashover voltage reduced with the increasing of salt deposit density on GFRP material, and the flashover voltage under negative switching impulse is less compared with positive switching impulse.…”
Section: Introductionmentioning
confidence: 99%
“…The research carried by Douar [5] indicated that pollution deposit on the surface of insulator reduces the flashover voltage, irrespective of the polarity of applied voltage. Kumar [6] found that the flashover voltage reduced with the increase of the salt deposit density on the glass fiber reinforced plastic (GFRP) material. Holboell [7] found that wet polluted surface of blade had an increasing tendency of streamer attraction.…”
Section: Introductionmentioning
confidence: 99%